Impact of Green Marketing on Consumer Buying Behavior: The Mediating Role of Environmental Knowledge: A Study of Surkhet District - Nabin Gaire, (Journal of Nepalese Management and Research, 2024)
This research addresses a significant gap in the literature regarding the impact of green marketing activities such as eco-labeling, green branding, and green advertising on consumer buying behavior, considering the mediating role of environmental knowledge. The study investigates the level of environmental awareness among consumers in Surkhet, a developing area, and analyzes how these green marketing practices influence purchasing decisions. Findings indicate that educated consumers in Surkhet exhibit high environmental awareness, with green branding and green advertising significantly enhancing consumer buying behavior, while eco-labeling shows no meaningful effect. Additionally, environmental knowledge positively impacts consumer buying behavior and partially mediates the relationship between green marketing initiatives and purchasing patterns. These results align with previous research in other developing countries, highlighting the effectiveness of marketing strategies in shaping consumer decisions. This study offers valuable insights into the interplay between green marketing and consumer behavior, emphasizing the importance of environmental knowledge, and suggesting targeted strategies for policymakers and marketers to promote sustainable practices and environmentally friendly purchasing behaviors.